Glyphosate in water bodies: environmental problem - Zirena Vilca, Franz (2018)
The need to increase food production in the world is creating more extensive agricultural systems, featured by large scales of production, where the control of pest and weeds are made through the application of chemical products. Many of them belong to a technological package that is the case of glyphosate in the cultivation of transgenic soy; given its high efficiency in the control of invasive plants, however, residues of this product can contaminate several compartments of the ecosystem, the aquatic ecosystem being the most affected. Therefore, several adverse effects of this compound will be addressed to organisms that inhabit this ecosystem.